A study on changing performance intentions during different stages of psychological contracts - K V, Santhosh; Vikas, Bhavya (International Journal of Innovative Research and Scientific Studies, 2025)
The purpose of this study is to determine whether performance intention varies among employees during pre-employment, early socialization, and later stages of psychological contracts (PC). This research aims to assist contemporary organizations in strategizing and customizing employee engagement according to different stages of PC. To test the hypothesis, data were collected using a structured questionnaire from 180 respondents across various age groups to represent different stages of PC. The first group consisted of final-year postgraduate students with no work experience; the second group included individuals with less than five years of work experience; and the third group comprised those with more than ten years of work experience. These respondents were selected through mixed-mode sampling. To theoretically represent the relationships between variables, stock and flow diagrams were constructed, and statistical analysis was employed to validate these models. Internal consistency was assessed using Cronbach’s alpha. The association between variables was examined using correlation techniques. After observing the correlation results, ANOVA was conducted on SPSS to analyze the variances among the three groups. The analysis revealed that performance intentions differ significantly across stages, possibly due to varying levels of awareness about their employer, organizational culture, and practices. Consequently, it is recommended to tailor employee engagement strategies to each stage of PC to foster a strong workforce and achieve improved performance outcomes.